MANAJEMEN STRATEGI SEKOLAH UNTUK KEMITRAAN KELUARGA-SEKOLAH YANG BERKELANJUTAN: SEBUAH TINJAUAN SISTEMATIS - Siti Mukarromah; Silvi Rahmawati; Riskya Kasinta; Masita Urdiani; Mini Kurnia; Tuhmatul Mardiyah; Muh. Fahrurrozi; Muhammad Sururuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Family–school partnership is consistently associated with students’ academic, motivational, behavioral, and socio-emotional development, yet parental participation in many elementary schools remains episodic and event-centered. This systematic review examines how school management can transform parental involvement into a sustainable, reciprocal, and learning-oriented partnership. The review analyzed 24 records identified through a structured literature search and retained 16 studies that directly addressed school–parent collaboration, parental participation, communication, leadership, or partnership management in elementary education. Data were organized in a synthesis matrix and analyzed thematically. Six interdependent management domains emerged: relationship-centered leadership; inclusive, two-way communication; shared governance and co-design; parent capacity development; differentiated and context-responsive engagement; and institutional monitoring for continuity. Digital platforms broaden access and accelerate information exchange, but they are effective only when combined with relational trust, clear communication protocols, attention to digital inequality, and opportunities for meaningful parent agency. The review further indicates that successful partnerships extend beyond attendance at school events to include home-based learning support, joint decision-making, character development, student monitoring, and coordinated problem-solving. The article contributes an integrated management framework that positions parental engagement as an organizational outcome deliberately produced through planning, role clarification, implementation, evaluation, and continuous improvement. Because the original evidence base was limited in database coverage and methodological diversity, future reviews should employ multiple international databases, formal quality appraisal, and transparent PRISMA reporting.